2020
DOI: 10.1002/jmv.26279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical exacerbation of SARS‐CoV2 infection after fingolimod withdrawal

Abstract: The role of disease‐modifying therapies in patients with autoimmune disorders during SARS‐CoV2 infection is controversial. Immunocompromised patients could have a more severe COVID‐19 disease, due to the absence of an adequate immune response against the SARS‐CoV‐2. However, therapies that act on immune response could play a protective role by dampening the cytokine release syndrome. Fingolimod is a drug used for immune therapy in patients with Multiple Sclerosis (MS) through the sequestration of activated lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…On the other hand, blunting the immune response and potential of sphingosine-1-phosphate enhancing the lung endothelial cell integrity may be the possible explanations that make Fingolimod a potential therapy to control the severe respiratory disease. ( Figure 2 )Gomez-Mayordomo V et al ( Gomez-Mayordomo et al, 2020 ) reported a case of clinical exacerbation of SARS-CoV2 infection after Fingolimod withdrawal in a 57-year-old man with RRMS and EDSS 6.0. The patient showed hyper-inflammation syndrome one week after Fingolimod withdrawal, and he progressively improved following steroid therapy.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, blunting the immune response and potential of sphingosine-1-phosphate enhancing the lung endothelial cell integrity may be the possible explanations that make Fingolimod a potential therapy to control the severe respiratory disease. ( Figure 2 )Gomez-Mayordomo V et al ( Gomez-Mayordomo et al, 2020 ) reported a case of clinical exacerbation of SARS-CoV2 infection after Fingolimod withdrawal in a 57-year-old man with RRMS and EDSS 6.0. The patient showed hyper-inflammation syndrome one week after Fingolimod withdrawal, and he progressively improved following steroid therapy.…”
Section: Resultsmentioning
confidence: 98%
“…Overall, the data of 2493 MS patients and 37 NMOSD patients were reported with COVID-19. ( Table 1 , 2 ) ( Sahraian et al, 2020 , Safavi et al, 2020 , Bowen et al, 2020 , Louapre et al, 2020 , Dalla Costa et al, 2020 , Parrotta et al, 2020 , Barzegar et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Sahraian et al, 2020 , Nesbitt et al, 2020 , Chaudhry et al, 2020 , Castillo Álvarez et al, 2020 , Shalhoub, 2020 , Delbue et al, 2007 , Berger and Brandstadter, 2020 , Maillart et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Crescenzo et al, 2020 , Mehta et al, 2019 , Maghzi et al, 2020 , Möhn et al, 2020 , Bollo et al, 2020 , Ciardi et al, 2020 , Valencia-Sanchez and Wingerchuk, 2020 , Foerch et al, 2020 , Barzegar et al, 2020 , Chiarini et al, 2020 , Gomez-Mayordomo et al, 2020 , Mallucci et al, 2020 , Giovannoni et al, 2020 , Borriello and Ianniello, 2020 , Louapre et al, 2020 , Aguirre et al, 2020 , Rimmer et al, 2020 , Luna et al, 2019 , Carandini et al, 2020 , Matías-Guiu et al, 2020 , Guevara et al, 2020 , Fernández-Díaz et al, 2020 , Amor et al, 2020 , Fiorella and Lorna, 2020 , Dersch et al, 2020 , De Angelis et al, 2020 , Celius, 2020 , Jack et al, 2020 , Suwanwongse and Shabarek, 2020 , Ghajarzadeh et al, 2020 , Montero-Escribano et al, 2020 , Novi et al, 2020 , …”
Section: Resultsmentioning
confidence: 99%
“…It is likely safe to continue ongoing treatment during the pandemic provided the ALC is higher than 200/mm 3 and is likely safe (and potentially beneficial) to even do so in patients infected with COVID-19. Two cases of COVID-19 worsening after stopping fingolimod have been reported [56,57]. Treatment interruption may be considered if ALC goes below 200/mm 3 although the impact of this low level of circulating lymphocytes on infection risk is not well defined [58].…”
Section: Potential Relevance To the Covid-19 Pandemic And Possible Rimentioning
confidence: 99%
“…In the most severe case, high levels of IL-6 were reported and intubation was necessary. If discontinuation of fingolimod increased the risk of acute respiratory distress syndrome, or if fingolimod effect per se is attributable to this course, remains unknown [81][82][83][84][85]. Notably, two patients remained completely asymptomatic during COVID-19 infection [86].…”
Section: Glatiramer Acetatementioning
confidence: 99%